2010
DOI: 10.2169/internalmedicine.49.2964
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis

Abstract: Necrotizing fasciitis (NF) is a necrotizing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
1
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 64 publications
3
118
1
14
Order By: Relevance
“…괴사성 근막염은 산부인과 영역에 서 수술 창상에서 발생한 감염 중에 가장 중한 형태로 사망률이 보고자 에 따라 30%-50%에 이른다 [2,10]. 괴사성 근막염의 위험인자는 당뇨, 50세 이상의 연령, 말초 혈관질 환, 고혈압, 비만, 영양결핍, 면역 억제상태, 수술환자, 이전 방사선치 료의 기왕력 등이 있다 [6,11].…”
Section: 증 례unclassified
See 1 more Smart Citation
“…괴사성 근막염은 산부인과 영역에 서 수술 창상에서 발생한 감염 중에 가장 중한 형태로 사망률이 보고자 에 따라 30%-50%에 이른다 [2,10]. 괴사성 근막염의 위험인자는 당뇨, 50세 이상의 연령, 말초 혈관질 환, 고혈압, 비만, 영양결핍, 면역 억제상태, 수술환자, 이전 방사선치 료의 기왕력 등이 있다 [6,11].…”
Section: 증 례unclassified
“…괴사성 근막염의 위험인자는 당뇨, 50세 이상의 연령, 말초 혈관질 환, 고혈압, 비만, 영양결핍, 면역 억제상태, 수술환자, 이전 방사선치 료의 기왕력 등이 있다 [6,11]. 괴사성 근막염과 이외의 연부조직 감염 을 구분 하는 것은 매우 어렵지만 중요한 문제인데, 이는 괴사성 근막 염이 적극적인 수술적 조직 제거로 치료되어야 하는 수술적 응급 질환 이기 때문이다 [2]. 그러나 발병 부위의 압통, 홍반, 통증, 부종 같은 초 기 증상은 경증의 연부조직 감염과 증상이 비슷하여 조기 진단이 어렵 다 [11,12].…”
Section: 증 례unclassified
“…Wang Y et al Staged necrotising fasciitis based on the evolving cutaneous features [15] (TABLE 1). Many studies by Park et al [16], Hsiao et al [17], Huang et al [18], Frazee B et al [19], Dworkin M et al [20], Singh G et al [21], Shimizu T [22] , et al and Hakkarainen TW et al [23] have documented trauma including operative trauma with mono or polymicrobial infections, consumption of raw or undercooked seafood or injury by fish fins, seawater contamination of wounds infected with marine organisms as common aetiological factors. Many other authors [24][25][26][27][28][29] also reported similar conclusions on various spectrums of synergistic pathogenesis with polymicrobial infections including marine organisms in NF.…”
Section: Introductionmentioning
confidence: 99%
“…Se trata de una afectación rara, con una incidencia en adultos de 0,40 casos por cada 100.000 habitantes, aunque recientemente se ha observado un aumento exponencial en esta tasa (1).…”
Section: Introductionunclassified
“…La presencia de uno de los cinco últimos factores mencionados se relaciona con mayor frecuencia a la aparición de sepsis grave (1).…”
Section: Introductionunclassified